Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Kontekstual Pada Materi Ekosistem Kelas VII SMPN Tanjung Jabung Timur: The Development of Contextual Based Student Worksheet (LKPD) in the Material of Class VII Ecosystem, SMP Tanjung Jabung Timur - Yanto Sugiyanto; M. Haris Effendi Hasibuan; Evita Anggereni (Universitas Jambi, 2018)
Innovative and fun learning can be realized through various ways, one of which is by using relevant and interesting media. This study aims to produce a student learning worksheet based on the Contextual Teaching and Learning (CTL) approach on the ecosystem material for class VII, and to determine the effectiveness of the use of the student worksheet. This is a research and development research using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The development process data was collected using a validation questionnaire of design experts, material experts, teacher and student questionnaires and student learning outcomes data after using the worksheet. The results of the assessment by material experts obtained average value 3.11 (good category) while the assessment by media experts obtained average value 3.30 (very good category). Assessment by students gets average value 90.33 (very well category), the assessment by teacher gets average value 10.82 (very good categories). The use of the developed student worksheet in the learning process shows a significant increase in the average learning outcomes from 52.31 to 72.69 (increase 20.38). The produced student learning worksheet is declared appropriate for use in learning.